1980
DOI: 10.1111/1523-1747.ep12519991
|View full text |Cite
|
Sign up to set email alerts
|

Dermatosparaxis in a Himalayan Cat: I. Biochemical Studies of Dermal Collagen

Abstract: Dermatosparaxis, a genetic disease, results from the deficiency of the NH2 procollagen peptidase, an enzyme which removes the NH2-terminal nontriple-helical extensions from procollagen. We have identified a Himalayan cat which has deficient amino terminal procollagen peptidase activity. The partially processed precursor chains pNalpha 1 (110,000 daltons) and pNalpha 2 (99,000 daltons) were identified by sodium dodecyl sulfate electrophoresis. In contrast to that from a normal animal, the 20,000 xg supernatant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 17 publications
0
29
0
1
Order By: Relevance
“…11 Also, a recessive mode of inheritance of the disease was described in one Himalayan cat. 2,3,19 The biochemical alterations of EDS are manifest clinically as fragility and hyperextensibility of cutaneous tissue. 19 In some cases, it is possible to detect microscopic abnormalities of collagen fibers, whose ultrastructural aspects have been described for feline cutaneous asthenia.…”
Section: Figmentioning
confidence: 99%
“…11 Also, a recessive mode of inheritance of the disease was described in one Himalayan cat. 2,3,19 The biochemical alterations of EDS are manifest clinically as fragility and hyperextensibility of cutaneous tissue. 19 In some cases, it is possible to detect microscopic abnormalities of collagen fibers, whose ultrastructural aspects have been described for feline cutaneous asthenia.…”
Section: Figmentioning
confidence: 99%
“…SDS polyacrylamide gel electrophoresis of the soluble material which did not bind to DEAE-cellulose in peak 1 from the dwarf demonstrated the presence of type II collagen. Although growth plates from dwarf Malamutes were assessed for the presence of pro-collagen as described by Counts et al [29], no procollagen could be detected. Amino acid analysis of the material which did not bind to DEAE-cellulose in peak 1 indicated that the material was indeed type II collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Estas características cutâneas impedem que o animal seja mantido no sistema de criação, sendo descartado ou tirado de suas atividades habituais. Denominada em humanos como síndrome Ehler-Danlos tipo VIIC (Colige et al 1999) a dermatosparaxia já foi descrita em gatos (Counts et al 1980), cães (Panciello et al 2003), cavalos (Badial et al 2013), bovinos (Kawaguchi et al 1988, Colige et al 1999) e em algumas raças de ovinos (Fjolstad & Helle 1974, Ramshaw et al 1983, van Weeren-Keverling & Koeman 1986, van Halderen & Green 1988, Sucupira et al 2009, Vaatstra et al 2011, Zhou et al 2012. A dermatosparaxia em ovinos da raça White Dorper já foi descrita na África do Sul (van Halderen & Green 1988), Austrália (Aggs 2007), Espanha (Sucupira et al 2009), Nova Zelândia (Vaatstra et al 2011, Zhou et al 2012) e Estados Unidos (Grant & Patton 2012).…”
Section: Introductionunclassified